Elaphostrongylus spp. from Scandinavian cervidae - a scanning electron microscope study (SEM) - Stéen, Margareta; Johansson, Carina (Rangifer, 1990)
Nematodes of the genus Elaphostrongyluscollected from moose (Alces alces L.), reindeer (Rangifer tarandus tarandus L.), and red deer (Cervus elaphus L.), respectively, were studied by means of scanning electron microscopy. Morphological differences in the ribs of the genital bursa were demonstrated. The Elaphostrongylus species from reindeer and red deer differed from each other in four ribs of the genital bursa. These results agree with the morphological characters of E. cervi and E. rangiferi described by Cameron (1931) and Mitskevitch (1960). The genital bursa of Elaphostrongylus sp. from moose, in accordance with the description of E. alces by Steen et al. (1989) showed characteristics differing from those found in Elaphostrongylus spp. from reindeer and red deer respectively. These results support the hypothesis that there are three separate species of Elaphostrongylus present in Scandinavian Cervidae. Svep-elektroniska studier på Elaphostrongylus spp. hos skandinaviska hjortdjur.Abstract in Swedish / Sammandrag: Rundmaskar inom slaktet Elaphostrongylus funna hos alg (Alces alces L.), ren (Rangifer tarandus tarandus L.) och kronhjort(Cervus elaphus L.) studerades med hjalp av svepelelektronmikroskop. De hanliga bursorna med sin a stodjeribbor uppvisade variationer i utseende, langd och placering mellan dessa rundmaskar. De arter av Elaphostrongylus funna hos ren och kronhjort skilde sig åt avseende fyra stodjeribbor på de hanliga bursorna. Dessa resultat stammer val overens med de karaktarer som tidigare ar beskrivna av Cameron(1931) och av Mitskevich (1960). Den hanliga bursan hos arten Elaphostrongylus funnen hos alg, vilken tidigare ar beskriven av Steen et al. (1989), visade upp ett utseende som skilde sig från bursorna hos de Elaphostrongylus-arter funna hos ren och kronhjort. Dessa resultat stoder hypotesen om tre skilda arter av Elaphostrongylus hos skandinaviska hjortdjur.